The international prognostic score and HIV status predict red cell concentrate transfusion needs in Hodgkin lymphoma - Simba, Kudakwashe (Department of Medicine, 2026)
Despite the burden of anaemia among Hodgkin Lymphoma (HL) patients, data evaluating red cell concentrate transfusion is limited. We retrospectively studied 285 newly diagnosed HL patients who received first-line ABVD treatment at Groote Schuur Hospital, Cape Town. HIV prevalence in the cohort was 39.5% and 74.2% of patients had advanced stage HL. Patient prognosis was scored using the HL International Prognostic Score (IPS-7) and HL IPS-3. Seventy (24.6%) patients were transfused with a median of 2(IQR 1-5) units per patient. Compared to HIV-negative patients, more HIV-positive patients were transfused (14.1% vs 40.4%, P<0.001) and received more units, median 2(IQR 1-3) vs. 3(IQR 2-5), P=0.035. HL IPS-7 (OR 2.1, P<0.001) and HL IPS-3 (OR 2.6, P<0.001) were independently associated with transfusion. HL IPS-7, HL IPS-3 and HIV positivity remained associated with transfusion after adjusting for covariates. For patients with newly diagnosed HL, HL IPS-7, HL IPS-3 and HIV status predicted transfusion.